On the Co-Occurrence of Warm Conveyor Belt Outflows and PV Streamers* - Madonna, Erica; Limbach, Sebastian; Aebi, Christine; Joos, Hanna; Wernli, Heini; Martius, Olivia (Journal of the Atmospheric Sciences, 2014)
The co-occurrence of warm conveyor belts (WCBs), strongly ascending moist airstreams in extratropical cyclones, and stratospheric potential vorticity (PV) streamers, indicators for breaking Rossby waves on the tropopause, is investigated for a 21-yr period in the Northern Hemisphere using Interim European Centre for Medium-Range Weather Forecasts (ECMWF) Re-Analysis (ERA-Interim) data. WCB outflows and PV streamers are respectively identified as two- and three-dimensional objects and tracked during their life cycle. PV streamers are more frequent than WCB outflows and nearly 15% of all PV streamers co-occur with WCBs during their life cycle, whereas about 60% of all WCB outflows co-occur with PV streamers. Co-occurrences are most frequent over the North Atlantic and North Pacific in spring and winter. WCB outflows are often located upstream of the PV streamers and form earlier, indicating the importance of diabatic processes for downstream Rossby wave breaking. Less frequently, PV streamers occur first, leading to the formation of new WCBs.